The Effect of Using Sunflower Meal as A Protein Source Replacing Soybean Meal on Milk Production, Its Components and Some Blood Traits in Awassi Ewes - Dawood, Raghad Nabeel (Journal of agricultural, environmental and veterinary sciences, 2020)
The research was conducted to study the effect of the use of sunflower meal (SFM) as a protein source in Awassi ewe feeding diets on milk production, milk components, and biochemical blood characteristics. In the study, 18 Awassi ewes were used, ranging in age from (3-4) years, with an average weight of (49) kg. The ewes were randomly divided into three equal groups in their weight and milk production rates. The first group ewes were fed on a standard diet consisting of soybean meal, yellow corn, barley, wheat bran, wheat flour, salt, and limestone. The sunflower fraction replaced the soybean meal in the diets of the second and third groups by 7 And 14 %, respectively. The feeding period lasted for (90) days. The results showed that the ewes of the second group were the highly significant difference at a level (p ≤ 0.05) in daily and total body weight and final weight. The daily milk production rate in the second treatment was significantly different at a level (p ≤ 0.05), as it reached 0.601 kg/day from the third treatment, which reached 0.513 kg/day and mathematically from the first treatment in which the daily milk production reached 0.541 kg/day, the same significant difference was found in the second group of treatment in total milk production rates compared to other treatments was (48.69, 54.09 and 46.17) kg/ewes for the three treatments, respectively. The study also showed that the differences between the first (standard) treatment and the treatments in which sunflower was used were not in the rates of ratios of (fat, protein, lactose and total solids) of milk, while a significant increase at a level (p≤0.05)  was observed in the produced quantities of the protein (33.29 g / day) and the fat (43.09 g / day) of ewe milk of the second treatment compared to the quantities produced of the protein (27.44 g / day) and the fat (38.42 g / day) of the ewe milk that consumed the third diet. The analysis of biochemical blood samples did not differ significantly between the three treatments. The study recommends conducting research using a percentage higher than 14% for sunflower meal and knowing its effect on production, and conducting other studies to find out the effect of sunflower meal on the concentration and quality of fats in the tissues of carcasses and milk produced, in addition to conducting digestion experiments and knowing the rumen environment in Awassi sheep.
Keywords: Feed Diets Awassi Sheep; Milk Production; Sunflower meal